2010
DOI: 10.1111/j.1528-1167.2009.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia in epileptic patients on new antiepileptic drugs

Abstract: SUMMARYPurpose: Older enzyme-inducing antiepileptic drugs (AEDs) may induce supraphysiologic plasma concentrations of total (t) homocysteine (Hcy). The aim of the present study was to investigate the effect of new AEDs on plasma tHcy levels. Methods: Patients 18-50 years of age, on AEDs monotherapy, with no other known cause of hyper-tHcy were enrolled. Plasma tHcy, folate, vitamin B 12 , and AEDs levels were determined by standard high-performance liquid chromatography (HPLC) methods. Methylenetetrahydrofolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 45 publications
7
83
2
Order By: Relevance
“…The overall risk of bias in the studies was considered to be of moderate quality (supplementary Figure B), with only 9 studies using matched analyses or adjusting for confounding for factors like age and sex. (Belcastro et al, 2010;Calandre et al, 1992;Erminio et al, 1994;Hamed et al, 2007;Isojärvi et al, 2001;Luoma et al, 1982;Mintzer et al, 2009;Phabphal et al, 2012;Vilchez et al, 1999) …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The overall risk of bias in the studies was considered to be of moderate quality (supplementary Figure B), with only 9 studies using matched analyses or adjusting for confounding for factors like age and sex. (Belcastro et al, 2010;Calandre et al, 1992;Erminio et al, 1994;Hamed et al, 2007;Isojärvi et al, 2001;Luoma et al, 1982;Mintzer et al, 2009;Phabphal et al, 2012;Vilchez et al, 1999) …”
Section: Resultsmentioning
confidence: 92%
“…We selected 106 studies for full text review and adjudication, of which 31 studies were deemed appropriate for the final review (supplementary Figure A). (Belcastro et al, 2010;Calandre et al, 1992Calandre et al, , 1991Chuang et al, 2012;Dastur and Dave, Page 8 of 33 A c c e p t e d M a n u s c r i p t 1987; Elliott et al, 2007;Erminio et al, 1994;Genc et al, 2010;Hamed et al, 2007;Isojärvi et al, 2001Isojärvi et al, , 1993Kim et al, 2013;Kim and Lee, 2007;Luef et al, 2009Luef et al, , 2002Luoma et al, 1982Luoma et al, , 1980Luoma et al, , 1979bMintzer et al, 2012Mintzer et al, , 2009Morrell et al, 2003;Nikkilä et al, 1978;Nikolaos et al, 2004;Pelkonen et al, 1975;Phabphal et al, 2012;Pylvänen et al, 2006Pylvänen et al, , 2003Sudhop et al, 1999;Svalheim et al, 2010;Vilchez et al, 1999;Zeitlhofer et al, 1993) The agreement between reviewers was good (κappa = 0.80, 95% confidence interval 0.68 -0.91).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is characterized by recurrent spontaneous seizures, in addition to unpredictable and periodic occurrence of a transient alteration of behavior due to the disordered, synchronous and rhythmic firing of populations of brain neurons. It has been observed that presently available antiepileptic drugs do not provide cure nor prevent relapse and they are often associated with debilitating adverse effects [2]. Toxicity, intolerance, and lack of efficacy are the limitations of the current antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…All currently approved antiepileptic drugs have dose-related toxicity and idiosyncratic side effects [5][6][7][8][9][10][11]. Therefore, the search for a newer, more effective, more selective agent with lesser side effects continues to be an area of investigation of medicinal chemists worldwide.…”
Section: Introductionmentioning
confidence: 99%